Representasi Harapan dalam Novel Menunggu Musim Kupu-Kupu: Kajian Struktural - Fania, Shinta Gusti; Virna, Septia; Nabila, Salwa; Abdurahman, Abdurahman (TSAQOFAH, 2026)
The representation of hope in literary works is an important issue because it relates to how texts depict human resilience in facing suffering, limitations, and the uncertainty of life. This study aims to describe the representation of hope in Menunggu Musim Kupu-Kupu by Adi Zamzam through a structural study. This study employed a qualitative approach with a descriptive design based on structural analysis. The data source of this study was the text Menunggu Musim Kupu-Kupu, while the research data consisted of narrative excerpts, dialogues, events, and symbols that represent hope. Data were collected through reading and note-taking techniques and were then analyzed through the stages of data reduction, data presentation, structural interpretation, and conclusion drawing. The results show that hope is represented through the interrelationship of theme, characters and characterization, plot, setting, conflict, symbols, and message. The butterfly symbol becomes the dominant element that represents change, freedom, and the possibility of a new life. These findings contribute to the development of structural studies of Indonesian literature by emphasizing that intrinsic elements not only construct the story but also shape human meaning. The conclusion of the study emphasizes that hope in this work appears as an inner strength to survive and escape from oppressive situations.